2015
DOI: 10.1038/srep08547
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Biosensors Using Enhanced Fano Resonances in Capped Gold Nanoslit Arrays

Abstract: Nanostructure-based sensors are capable of sensitive and label-free detection for biomedical applications. However, plasmonic sensors capable of highly sensitive detection with high-throughput and low-cost fabrication techniques are desirable. We show that capped gold nanoslit arrays made by thermal-embossing nanoimprint method on a polymer film can produce extremely sharp asymmetric resonances for a transverse magnetic-polarized wave. An ultrasmall linewidth is formed due to the enhanced Fano coupling between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(75 citation statements)
references
References 42 publications
0
72
0
1
Order By: Relevance
“…These Fano sensors have considerable applications in the detections of the concentration of the bulk gas, liquid, and macromolecules layers. In recent years, the Fano sensors based on the SPP modes mainly focused on the periodic metallic array structures because of the easy fabrications and convenient experimental detections . In the large‐area uniform gold nanoslit arrays ( Figure a), the sharp Fano resonance was achieved, as shown in Figure b .…”
Section: Plasmonic Sensors Based On Fano Resonancesmentioning
confidence: 99%
“…These Fano sensors have considerable applications in the detections of the concentration of the bulk gas, liquid, and macromolecules layers. In recent years, the Fano sensors based on the SPP modes mainly focused on the periodic metallic array structures because of the easy fabrications and convenient experimental detections . In the large‐area uniform gold nanoslit arrays ( Figure a), the sharp Fano resonance was achieved, as shown in Figure b .…”
Section: Plasmonic Sensors Based On Fano Resonancesmentioning
confidence: 99%
“…Evidently, the equation shows the SPP's resonant wavelength is sensitive to the variation of the nanoslit period and environmental RI, which indicated that the nanoslit array can be used as SPP based sensors by properly tuning the period of P. Furthermore, as we all know that the CMs mainly affected by the metal film depth [22,34], so we calculated the influences of metal film depth on the transmission spectra as shown in Fig. 3(b).…”
Section: Eot Behavior In Metal Nanoslit Arraymentioning
confidence: 99%
“…The resonant peaks of λ 1 and λ 3 have slight red shift and the full width at half maximum (FWHM) become narrower with increasing the nanoslit periods, while the resonant peak of λ 2 has an obvious red shift and its FWHM has been broadened slightly with increasing nanoslit periods. The larger red-shift of the λ 2 is due to the array period directly impacts the SPP mode according to the following equation [22]:…”
Section: Eot Behavior In Metal Nanoslit Arraymentioning
confidence: 99%
See 1 more Smart Citation
“…Nanostencil lithography (NSL) based on shadow-masked patterning of the nanostructure [28], nanoimprint lithography that creates nanopatterns by the mechanical deformation of imprint resist [29], and interference lithography where an interference pattern is recorded in a photoresist material [30] are processes that can achieve market significance by offering simple, scalable, and cost-effective fabrication methods and have also the possibility of using flexible substrates. Nanoplasmonic structures such as hybrid nanocavities [31], nanopillars [32], or nanoslits [33] are examples of recently fabricated nanostructures using some of these processes. They show extremely high sensitivity performance (8066, 1010, and 926 nm RIU -1 with figures of merit of 179, 108, and 252, respectively) that even exceeds the theoretically predicted upper limit for conventional SPR sensors, leading to LSPR wavelength shifts large enough to produce color differences noticeable by the naked eye at very small refractive index changes.…”
Section: Introductionmentioning
confidence: 99%